EVALUASI PERTUMBUHAN DAN DAYA HASIL TIGA KULTIVAR PADI GOGO (Oryza sativa L.) AKIBAT PENGGUNAAN JARAK TANAM - Rohaeni, Nani (Jurnal Magrobis, 2017)
Evaluation of Growth and Yield On Three Cultivars R of Upland Rice (Oryza sativa L.) Due To Use Of Plant Spacing. The research aims to: (i). Studied the effect of plant spacing on growth and yield of three cultivars of upland rice (Oryza sativa L.). (ii). Get the right spacing for three cultiars of upland rice (Oryza sativa L.) in evaluation (iii) the influence of evironmental factors on the grownt and yield power of three cultivars of upland rice (Oryza sativa L.) in evaluation. The reserach was conducted on Maret up to September2016, in the village of Cipta Graha of Kaubun Sub-district of East Kutai Regency. Research design used a Randomized Block Design (RBD) with experimental factorial and each treatment has 3 replicated. The first factor is cultivar of Gedagai and Kunyit.While the second factor is plant spacing 20 x 20 cm, 20 x 25 cm, 25 x 25 cm, 25 x 30 cm, dan 30 x 30 cm. Analysis data using ANOVA tables with advanced test Least Significant Difference (LSD) level 5%.The research results showed no significant interaction between cultivar treatment and plant spacing.The influence of cultivars had a significant effect on plant height of 45 hst, number of tillers/hill, and total grain amount/panicle, whereas in the treatment of spacing significant effect on total number of tillers/hill, number of productive tillers/hill and 1000 grain weight. Kultivar Gedagai and kunyit have the highest potential yield of successive respectively 1,483 Mg ha-1 and 1,319 Mg ha-. Treatment of plant spacing 25cmx25cm has the highest ppotential yield ie 1,430 Mg ha-1. All observed characters are influenced by environmental factors (h2 < 0,5).Keywords: Gedagai, Kunyit, Upland rice